AS EXPRESSÕES IDIOMÁTICAS NOS LIVROS DIDÁTICOS DE LE/LA E INTERCULTURALIDADE: UMA DISCUSSÃO A PARTIR DA PERSPECTIVA SOCIOCULTURAL - Hogetop, Mônica (WEB REVISTA SOCIODIALETO, 2019)
A partir dos estudos da Linguística Aplicada Crítica (LAC), mais concretamente nas perspectivas críticas de ensino de línguas e da interculturalidade, analisamos as expressões idiomáticas (EIs) empregadas em livros didáticos (LDs) de inglês. Para analisar os elementos culturais constituintes das EIs e proceder a sua categorização de acordo com a sua carga cultural e potencial de expressividade recorremos a uma perspectiva de investigação sociocultural. Como referenciais teóricos para a discussão fundamental da relação entre língua e cultura, baseamo-nos principalmente em Kramsch (1993, 1998, 2003, 2006, 2013) e Byram (1997). No que diz respeito à interculturalidade, especificamente à comunicação e à competência intercultural, tomamos como referencial teórico os estudos que mostraram que os LDs de inglês empregam as EIs com objetivos distintos para o ensino de LE-LA. Para definirmos uma EI, usamos as definições de Xatara (1998), de Pedro (2007) e do Quadro Comum Europeu de Referências para Línguas (2001). Os resultados mostram que os LDs analisados não fornecem recursos para a discussão e reflexão em torno da cultura de origem dos aprendizes e a cultura aprendida. Concluímos que a cultura e a variedade linguística estadunidenses prevalecem hegemônicas como modelo dos aprendizes. ABSTRACT: From studies of Critical Applied Linguistics on, this doctoral thesis aims at analyzing the idiomatic expressions used in two English textbooks: Smart Choice 2A and TopNotch2. The corpus was generated through an interpretativist investigation of documental type. From a sociocultural perspective, we analysed the cultural elements that constitute the idiomatic expressions and classified them according to their cultural load and expressivity potential. As theoretical references for the fundamental discussion of the relationship between language and culture, we based ourselves specially on Kramsch (1993, 1998, 2003, 2006, 2013), Byram (1997) and Pennycook (2006). As far as interculturality is concerned, specifically communication and intercultural potential, we took as theoretical references the work of Byram (1997) and Lange (2011).To define an idiomatic expression, we used the definitions of Xatara (1998), Pedro (2007) and the Common European Framework of References for Languages (2001), among others. The results show that the English textbooks use idiomatic expressions with distinct objectives. While the Top Notch2 textbook approaches the cultural aspects simultaneously to the linguistic aspects (culture in language representation), the Smart Choice2A textbook approaches them in parallel (language and culture representation). The analyzed idiomatic expressions are contextualized in informal language dialogues and conversations revealing cultural traits of the USA’s culture. Both textbooks do not promote discussion and reflection related to the learner’s culture and the learned culture. We also analyzed the types of cultural information found in the textbooks units and their relation to the linguistic items presented. KEYWORDS: Idiomatic expressions, culture, language, foreign and additional language teaching, textbooks.